Properties of potassium dihydrogen phosphate and its effects on plants and soil - Jančaitienė Kristina; Šlinkšienė Rasa; Žvirdauskienė Renata (Open Agriculture, 2023)
One of the challenges of the modern world is to improve human nutrition and to safely increase the yield of agricultural production using existing agricultural land. It is clear that sufficient agricultural efficiency cannot be achieved without fertilizers, but fertilizers must cause minimal damage to the soil. Microorganisms, such as spore-forming bacteria, actinomycetes, fungi, algae, and protozoa play an important role in the soil and keep soil healthy. One of the soil substances involved in reactions that take place in plants is cellulose. This study investigated the effect of potassium dihydrogen phosphate (PDP), synthesized (via conversion between potassium chloride and ammonium dihydrophosphate) and granulated with the addition of microcrystalline cellulose (MC), on plants (winter wheat Toras, Lithuania) and soil microorganisms. The data of plants fertilized with pure KH2PO4, ones fertilized with PDP granulated with MC, and grown without fertilizers were compared in this study. Scanning electron microscopy and differential scanning calorimetry analysis were used to characterize the obtained product. One-way analysis of variance was used to evaluate the differences of the mean values between groups. In all cases, the significance level was p ≤ 0.05. The effect of pure KH2PO4 on plant indicators was found to be lower than that of granular PDP with MC. The length of the leaves was 29.63 and 31.20 cm, green mass was 0.471 and 0.763 g, ash mass was 0.015 and 0.019 g, respectively. In addition, granular PDP with MC did not adversely affect the soil microorganisms because the number of any species of bacteria (Spore b., mineral nitrogen assimilating bacteria, cellulose degrading bacteria) did not decrease and a slight increase in the number of Actinomycetes (from 8.5 × 105 to 2.9 × 106 KSV/g) and molds (from 3.0 × 104 to 1.4 × 105 KSV/g) was observed. The granular PDP with MC that we developed and used have better physical properties, higher agrochemical efficiency and cause less harm to soil microorganisms compared to pure PDP.